Pengaruh Project Based Learning terhadap Peningkatan Kemampuan Berpikir Kreatif dan Self-efficacy - Elok Deswiana Hayati; Tri Jalmo; Berti Yolida (Universitas Lampung, 2019)
This study aims to determine the effect of Project Based Learning on self-efficacy and the ability to think creatively. The study design used non-equivalent pretest-posttes. The samples in the study were VIIH class as a control class and VIIE class as an experiment. Data on self-efficacy were obtained through a scale that were analyzed qualitatively. The ability of creative thingking obtained from the pretest, posttest and assessment of creative products which were analyzed using the Independent Sample t-Test. The results of the study showed that the ability creative thingking in the experimental class was is